Citrus aurantium increases seizure latency to PTZ induced seizures in zebrafish thru NMDA and mGluR's I and II - Rosa-Falero, Coral; Torres-Rodríguez, Stephanie; Jordán, Claudia; Licier, Rígel; Santiago, Yolimar; Toledo, Zuleyma; Santiago, Marely; Serrano, Kiara; Sosa, Jeffrey; Ortiz, José G. (Frontiers in Pharmacology, 2015)
Citrus aurantium (CA), commonly known as bitter orange, is used in folk medicine to treat anxiety and insomnia. Studies performed with Essential oils from the peel of the fruit have shown to increase seizure latency to pentylenetetrazole (PTZ) and maximal electroshock seizure in animal models. With these experiments, we assessed a possible role of an aqueous extract from the leaf of the Citrus aurantium tree. Anticonvulsant properties of C. aurantium extracts were tested using adult zebrafish (Danio rerio). Zebrafish exposed to C. aurantium 28 mg/ml showed a 119 % increase on seizure latency compared to controls. We evaluated GABAA and glutamate receptors as mediators of this increase in seizure latency. We used the selective antagonist gabazine to rule out GABAA receptors as targets for the C. aurantium extract. With glutamate receptors, we used two approaches, an In vitro ligand binding assay and the In vitro model of PTZ induced seizures in zebrafish combined with selective receptor antagonists. The ligand binding assay revealed C. aurantium extracts at concentrations of 0.42mg/ml to 5.6mg/ml significantly reduced [3H]Glu binding and this interaction showed to be selective for iGluR and mGluR group II and III. This pattern of interactions was evaluated In vivo pretreating zebrafish with glutamate receptor antagonists and we confirmed NMDA and mGluR’s I and II are involved with the mechanism of C. aurantium extract. These study results support the relevance of natural products as feasible alternatives for drug development providing evidence of effectiveness and possible mechanism of action for the extract.